2002
DOI: 10.1007/s100720200059
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and multiple sclerosis

Abstract: Several studies indicate that patients with multiple sclerosis (MS) have low serum levels of the endogenous antioxidant uric acid (UA), although it has not been established whether UA is primarily deficient or secondarily reduced due to its peroxynitrite scavenging activity. We measured serum urate levels in 124 MS patients and 124 age- and sex-matched controls with other neurological diseases. In addition, we compared UA levels when MS patients were stratified according to disease activity (by means of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 0 publications
11
47
2
1
Order By: Relevance
“…Some studies have suggested that serum or CSF UA levels decrease in MS (Dujmovic et al., 2009; Peng et al., 2008; Sotgiu et al., 2002), while others show increased UA and purine compounds in biological fluids of MS patients (Amorini et al., 2009; Langemann, Kabiersch, & Newcombe, 1992; Lazzarino et al., 2010). Min et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have suggested that serum or CSF UA levels decrease in MS (Dujmovic et al., 2009; Peng et al., 2008; Sotgiu et al., 2002), while others show increased UA and purine compounds in biological fluids of MS patients (Amorini et al., 2009; Langemann, Kabiersch, & Newcombe, 1992; Lazzarino et al., 2010). Min et al.…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress is also thought to be involved in NMO and MS (Gonsette, 2008; Haider, 2015; Lassmann & van Horssen, 2016; Penton‐Rol et al., 2009). Previous studies have focused more on serum UA in NMO/MS patients (Ashtari, Bahar, Aghaei, & Zahed, 2013; Liu et al., 2013; Min et al., 2012; Peng et al., 2008; Sotgiu et al., 2002), although cerebrospinal fluid (CSF) UA levels might more directly reflect CNS. However, very little is known about CSF UA levels in NMOSDs.…”
Section: Introductionmentioning
confidence: 99%
“…Changes of uric acid: in the course of MS a reduced value of uric acid (UA) was found, in normal range, compared to healthy subjects, in the absence of correlations with disease activity, duration, course or degree of disability [10]. This study favored the view that reduced UA in MS acts as a primary, constitutive loss of protection against oxidative agents.…”
Section: Introductionmentioning
confidence: 56%
“…This product may be responsible for a significant proportion of the damage attributed to NO and therefore may be an important factor in the generation of CNS lesions. Several studies suggest lower levels of serum UA in MS patients (7)(8)(9). In the other hand, there were several reports concerning no correlation with lower levels of serum UA, in the literature (10).…”
Section: Introductionmentioning
confidence: 99%